POTENȚIALUL TURISMULUI RURAL ÎN PRMOVAREA REPUBLICII MOLDOVA CA DESTINAȚIE TURISTICĂ - Hămuraru, Maria; Țurcanu, Natalia (CEP USM, 2023)
The real positive impact of rural tourism depends, very much, on the quality of the tourist services offered, and the way the villages are organized and laid out. Without the implementation of long-term development strategies, the reduction of mass tourism, the valorization of ecological agro-food products and the preservation of cultural identity, the social-economic effects will remain diminished. In this case, knowing all the complications regarding the practical application of rural tourism will certainly guide towards a realistic approach to the local possibilities in offering tourist services, as well as the coordination of the community's efforts for a generally prosperous future.
THE POTENTIAL OF RURAL TOURISM IN PROMOTING THE REPUBLIC OF MOLDOVA AS A TOURIST DESTINATION
Keywords: sustainable development; public sector